Rapid loss of self‐incompatibility in experimental populations of the perennial outcrossing plant Linaria cavanillesii. (28th March 2019) - Voillemot, Marie; Encinas‐Viso, Francisco; Pannell, John R.
Abstract: Transitions from self‐incompatibility to self‐compatibility in angiosperms may be frequently driven by selection for reproductive assurance when mates or pollinators are rare, and are often succeeded by loss of inbreeding depression by purging. Here, we use experimental evolution to investigate the spread of self‐compatibility from one such population of the perennial plant Linaria cavanillesii into self‐incompatible (SI) populations that still have high inbreeding depression. We introduced self‐compatible (SC) individuals at different frequencies into replicate experimental populations of L. cavanillesii that varied in access to pollinators. Our experiment revealed a rapid shift to self‐compatibility in all replicates, driven by both greater seed set and greater outcross siring success of SC individuals. We discuss our results in the light of computer simulations that confirm the tendency of self‐compatibility to spread into SI populations under the observed conditions. Our study illustrates the ease with which self‐compatibility can spread among populations, a requisite for species‐wide transitions from self‐incompatibility to self‐compatibility.